Dramaturgy and the Phenomenon of Instagram Multi-Account Usage Among Gen Z in Bali - Winduwati, Septia; Irena, Lydia (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Generation Z, born between 1997 and 2012, has grown up in a digital technology era that has shaped their communication and interaction styles, particularly through social media platforms like Instagram. They are highly active on this platform, with 58% spending more than an hour each day. This study aims to analyze how Generation Z utilizes multiple accounts on Instagram using Erving Goffman's dramaturgical theory, which describes social interactions as performances where individuals play roles according to social contexts. This research is expected to contribute to understanding the construction of digital identities and social roles of Generation Z. A qualitative approach is used in this study to describe the findings from Generation Z Instagram users with multiple accounts in Bali. Data were collected through in-depth interviews, field observations, and document studies, and analyzed using thematic analysis techniques. The results indicate that Generation Z uses multiple Instagram accounts to separate